Between Adolescence and Adulthood: Emerging Adulthood in Serbia - Jojić, Antonije (Psihološka istraživanja, 2024)
Jeffrey Arnett defines emerging adulthood (EA) as a developmental period set between adolescence and adulthood. Research conducted in different countries mostly confirms the presence of EA dimensions around the world with certain discrepancies which are believed to reflect the cultural and socioeconomic differences between nations. Our research set out to examine the presence of emerging adulthood in Serbia by exploring differences between age groups (adolescents, emerging adults, adults) in relation to dimensions of EA and Markers of Adulthood, as well as the psychometric characteristics of the IDEA scale. The participants were 1049 young people (78,6% female) aged 18 to 30 (M = 23,72, SD = 3,212), mostly from major cities. Factor analysis, for the most part, confirmed the structure of the IDEA scale. Results suggest that the indicators of emerging adulthood are more pronounced among emerging adults compared to adults (significant differences on 5/6 IDEA subscales). Compared to adults, emerging adults are more likely to describe the current phase of their lives as unpredictable, undefined, and driven by exploration and a search for answers and meaning. On the other hand, adults have shown a more other-oriented approach and a higher degree of self-sufficiency. Finally, emerging adults have shown themselves to be more self-focused than adolescents. Measures of adulthood point to significant differences between age groups on 3/4 indicators. Adults are more likely to view themselves as independent, autonomous and relationally mature, compared to younger age groups.